Study on construction of transformation vectors carrying contructs of rol genes highly effective in plant hairy roots induction - Ngoc, Le Thu; Trang, Tran Thu; Ngoc, Pham Bich; Ha, Chu Hoang; Nhut, Duong Tan (Academia Journal of Biology, 2014)
Culture of hairy roots the roots induced by infecion of Agrobacterium rhizogenes into wounded plant tissues has long been widely applied in many research fields such as functional analysis of genes, expression of foreign proteins, production of secondary compounds or changes of the composition of metabolites in plants. The causes of hairy root formation were identified related to the TL-DNA on Ri plasmids of A. rhizogenes strains, in which 4 gene loci including rolA, B, C and D (root loci) play important roles. However, expression of these rol genes in single form or in combination greatly affects the frequency of hairy root formation as well as the growth and morphology of the roots. In this study, we established, evaluated and selected the transgenic constructs of rol genes highly effective in plant hairy root induction. Single rolB, rolC genes and a combination of rolA, B, C were amplified from DNA template as Ri plasmid extracted from A. rhizogenes strain ATCC 15834 by PCR using specific primers linked with recognition sequences of restriction enzymes. The two genes rolB, rolC and the multi-gene segment rolABC were then introduced into pBI121 and pCB301 vectors, respectively, to yield recombinant plasmids and were transformed into A. tumefaciens C58/PGV 2260. The results of transgenesis for induction of hairy roots on leaves of tobacco via Agrobacterium strains carrying the three constructs of rol genes showed that: the simultaneous expression and interaction of rolA, B and C resulted in the highest frequency of hairy root formation in transgenic tissues (over 60%), and the roots displayed all typically morphological characteristics of hairy roots. In the transgenic tissues containing single rolB, root formation frequency was only about 20%. Moreover, the speed of growth and density of branches were also lower. Meanwhile, individual activity of rolC hardly induced hairy root phenotype.